2009
DOI: 10.1002/acp.1595
|View full text |Cite
|
Sign up to set email alerts
|

Memory distrust and acceptance of misinformation

Abstract: Relying on a community sample (N ¼ 80), the present study examined whether memory distrust is related to an increased tendency to accept misinformation and whether it interacts with passage of time. Participants were shown video footage of an armed robbery. Approximately 30 minutes later, they were asked to describe as accurately as possible what they had seen. Either 1 day or 2 weeks later they were presented with their own statements, to which five misinformation items had been added. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 38 publications
(45 reference statements)
8
48
0
Order By: Relevance
“…Further analyses showed that the main reason for this behavior was that participants doubted their own memory. The finding that trusting one's memory may be an important predictor of accepting misinformation was confirmed by van Bergen, Horselenberg, Merckelbach, Jelicic and Beckers (2010).…”
Section: Introductionsupporting
confidence: 64%
“…Further analyses showed that the main reason for this behavior was that participants doubted their own memory. The finding that trusting one's memory may be an important predictor of accepting misinformation was confirmed by van Bergen, Horselenberg, Merckelbach, Jelicic and Beckers (2010).…”
Section: Introductionsupporting
confidence: 64%
“…Judging from participants' private statements towards another confederate, 55% of the participants who were confronted with false evidence actually internalized their confessions, compared with 6% in the group without false witness evidence. The memory corrupting effect of false evidence has also been observed in other studies (e.g., Horselenberg, Merckelbach, & Josephs, ; van Bergen, Jelicic, & Merckelbach, ), and some authors have argued that it is primarily carried by false evidence promoting a state of memory distrust, in which people become more willing to confess to things that they did not do (van Bergen, Horselenberg, Merckelbach, Jelicic, & Beckers, ).…”
Section: Introductionsupporting
confidence: 64%
“…Future research addressing this prediction would further contribute to our understanding of the links between memory suggestibility and metamemorial beliefs. In fact, whereas people who trust their memories tend to be less susceptible to suggestion, the present data suggest that these same people might also be less likely to systematically test and validate their memories, meaning that the memory errors they do commit may be more likely to endure (e.g., Van Bergen, Horselenberg, Merckelbach, Jelicic, & Beckers, 2010).…”
Section: Discussionmentioning
confidence: 61%